2013
DOI: 10.3390/md11114419
|View full text |Cite
|
Sign up to set email alerts
|

Crambescidin-816 Acts as a Fungicidal with More Potency than Crambescidin-800 and -830, Inducing Cell Cycle Arrest, Increased Cell Size and Apoptosis in Saccharomyces cerevisiae

Abstract: In this paper, we show the effect of crambescidin-816, -800, and -830 on Saccharomyces cerevisiae viability. We determined that, of the three molecules tested, crambescidin-816 was the most potent. Based on this result, we continued by determining the effect of crambescidin-816 on the cell cycle of this yeast. The compound induced cell cycle arrest in G2/M followed by an increase in cell DNA content and size. When the type of cell death was analyzed, we observed that crambescidin-816 induced apoptosis. The ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Rubiolo and colleagues investigated the guanidine antifungal alkaloid crambescidin-816 ( 51 ), previously isolated from the Mediterranean sponge Crambe crambe [62]. Detailed cell cycle studies in the yeast Saccharomyces cerevisiae demonstrated that this compound induced G2/M cell cycle arrest followed by apoptosis and mitochondrial disfunction, suggesting that although cytotoxic crambescidin-816 “….could serve as a lead compound to fight fungal infections”.…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Rubiolo and colleagues investigated the guanidine antifungal alkaloid crambescidin-816 ( 51 ), previously isolated from the Mediterranean sponge Crambe crambe [62]. Detailed cell cycle studies in the yeast Saccharomyces cerevisiae demonstrated that this compound induced G2/M cell cycle arrest followed by apoptosis and mitochondrial disfunction, suggesting that although cytotoxic crambescidin-816 “….could serve as a lead compound to fight fungal infections”.…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Several of these molecules have been patented due to their cytotoxic, antifungal and antiviral activities and some of them, as for example crambescidin 816 (C816), also have recognized effects over calcium ion channels [3, 5, 6]. Furthermore, in 2007 crambescidin 800 (C800) was also proposed as an antioxidant agent against hypoxia, nitric oxide and glutamate-induced oxidative stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to TGA class 3, TGA class 2 is less active, although batzelladine C ( 28 ) and L ( 38 ) and dehydrobatzelladine C ( 35 ), in general, exhibited a GI 50 below 1 µg/mL [ 73 ]. Finally, crambescidin 816 ( 3 ) was shown to inhibit cell migration by altering the cytoskeleton dynamics and induced cell death by apoptosis [ 75 , 78 ].…”
Section: Biological Activitiesmentioning
confidence: 99%